Effects of european monetary union on european and Turkish banking sector - Güler, Yiğit (My University, 1999)
Since The Bretton Woods System, The EMU is a very important economic and political event. Eleven member countries will lock their exchange rates irrevocably ant the national central banks will leave their authority to the newly created ECB.Simply it implies the loss of national monetary autonomy. At the macroeconomic level decrease in deficits below 3% will create a room for fiscal stabilizers to offset cyclical turns. In addition to that some price and wage changes can be needed. The size of the member states, level of integration, their share in the world trade volume will effect the world economy without a doubt. Turkey that is in Customs Union and has strong economic and financial relations with EU will also be affected from EU. On balance, The Treaty has been ratified by all Member States and Convergence under the Maastricht criteria is also under way. In the lightment of these issues, in the first part the historical settings of European Union are mentioned. In the second part, Institutions of European Union such as European Council, Commission , Parliament are mentioned. A s a third part the historical settings of EMU, Convergence criteria, tasks and organizations of the ESCB and EMI are mentioned. In the fourth part ,Economics of Europe is analyzed. As a fifth part Structural Features and Trends of Banking in Euro Area mentioned. In the sixth part, Effects of EMU in the Euro Area on issues such as Banking profitability,capacity, structure, strategies and risks. A s a next part Turkish Economy is considered. In the eighth part The Turkish Banking Sector is analyzed. Lastly, Effects of EMU on Turkish Banking Sector are mentioned.
Keywords: AVRUPA PARA BİRİMİ; Döviz; DÖVİZ; Ekonomi; Finansman ekonomisi; Para